Letter from Georg Bredig to Max Bredig, October 3, 1936 - Bredig, Georg (1936)
Georg Bredig (1868-1944) updates his son, Max Bredig (1902-1977) on family and health matters, and additionally inquires about Max's professional prospects abroad.
Keywords: Bredig, Georg, 1868-1944; Bredig, Max Albert, 1902-1977; Germany--Karlsruhe; Jews, German